ANTI-HYPERTENSIVE EFFECT OF THE DIPEPTIDE, TYROSYL-PROLINE, IN RVLM; A MICROINJECTION STUDY. (April 2021) - Zahid, Hasan Md.; Fujikawa, Koichi; Ohara, Hiroki; Okamoto, Kenji; Nabika, Toru
Abstract : Objective: Oligo-peptides were shown to have various physiological effects in-vivo. In this study, we evaluated antihypertensive activity of a dipeptide, tyrosyl-proline (YP), which was found in fermented milk at high concentration. Design and method: To evaluate effects of YP in CNS, YP was micro-injected into the rostral ventrolateral medulla (RVLM), the nucleus in the brainstem regulating blood pressure (BP), and changes in intra-arterial BP were monitored directly with a catheter inserted in the femoral artery in anesthetized rats. This study was supported by the Research Program on Development of Innovative Technology of the Bio-oriented Technology Research Advancement Institution, NARO. Results: YP microinjection into RVLM reduced BP in a dose-dependent manner. BP reduction at 100 pmole of YP was 41 ± 3 mmHg in SHRSP, which was as strong as that of LVY and IPP, both of which were known to have a potent anti-hypertensive effect. BP decrease was much smaller in WKY (7 ± 2 mmHg). Different sequences of dipeptide composed of tyrosine and proline (PY, YY and PP) showed much less effect on BP, excluding a possibility that the effect of YP on BP was non-specific. Naloxone (a non-specific inhibitor of opioid receptors) and nor-binaltorphimine (a selective inhibitor of kappa opioid receptor) antagonized the effect of YP, whereas naltrindole (a selective inhibitor of delta opioid receptor) failed to block it. This result implied that the effect of YP in RVLM was mediated by kappa opioid receptor. Conclusions: YP might play an important role in regulation of BP in RVLM through opioid receptors.